al-Kharīf al-ʻArabī fī al-tanāquḍ bayna al-thawrah wa-al-dīmuqrāṭīyah / Ayman al-Būghānmī. - Būghānmī, Ayman. (al-Silsilah al-fikrīyah wa-al-sīyāsīyah, 2015)
Arab countries; protest movements; democracy; history; 21st century.